2003
DOI: 10.1172/jci200317443
|View full text |Cite
|
Sign up to set email alerts
|

WNK kinases regulate thiazide-sensitive Na-Cl cotransport

Abstract: Pseudohypoaldosteronism type II (PHAII) is an autosomal dominant disorder of hyperkalemia and hypertension. Mutations in two members of the WNK kinase family, WNK1 and WNK4, cause the disease. WNK1 mutations are believed to increase WNK1 expression; the effect of WNK4 mutations remains unknown. The clinical phenotype of PHAII is opposite to Gitelman syndrome, a disease caused by dysfunction of the thiazide-sensitive Na-Cl cotransporter. We tested the hypothesis that WNK kinases regulate the mammalian thiazide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 17 publications
3
77
0
1
Order By: Relevance
“…One of the cardinal manifestations of FHHt is increased sensitivity to thiazide diuretics (14), suggesting that WNK kinases regulate the NCC. WNK4 was shown to inhibit NCC activity by reducing NCC abundance at the plasma membrane of Xenopus oocytes and mammalian cells (15)(16)(17)(18)(19). WNK1 indirectly regulates NCC by inhibiting WNK4, providing support for the hypothesis that a predominant mechanism by which WNK kinases control blood pressure and electrolyte balance is via effects on NCC.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…One of the cardinal manifestations of FHHt is increased sensitivity to thiazide diuretics (14), suggesting that WNK kinases regulate the NCC. WNK4 was shown to inhibit NCC activity by reducing NCC abundance at the plasma membrane of Xenopus oocytes and mammalian cells (15)(16)(17)(18)(19). WNK1 indirectly regulates NCC by inhibiting WNK4, providing support for the hypothesis that a predominant mechanism by which WNK kinases control blood pressure and electrolyte balance is via effects on NCC.…”
Section: Introductionmentioning
confidence: 88%
“…In contrast to effects of other WNK kinases on transport proteins, most of which are inhibitory, the WNK3 effect on NCC is stimulatory (20). We have reported previously that WNK1, WNK4, and KS-WNK1, a kidneyspecific splice form of WNK1, form protein complexes and interact functionally (15,(21)(22)(23). WNK1 can inhibit the effects of WNK4 on NCC, and KS-WNK1 can inhibit the effects of WNK1 on WNK4 and, indirectly, NCC.…”
Section: Introductionmentioning
confidence: 96%
“…WNK1 is expressed ubiquitously and is particularly associated with chloride-transporting epithelia at all sites (35), whereas WNK4 expression is limited to the distal nephron. Of particular interest here is recent evidence that WNK4 acts as a negative regulator of NCCT function (36,37). Disease-causing mutations relieve this inhibition, leading to transporter overactivity.…”
Section: Gordon Syndromementioning
confidence: 99%
“…It was reported that in Xenopus oocytes, WNK4 inhibits the activity of the sodium chloride cotransporter and that PHA2-causing WNK4 mutants fail to inhibit the sodium chloride cotransporter (7,8). Others reported that in cultured epithelial cells, WNK4 phosphorylates tight-junction proteins claudins 1-4 and regulates the paracellular chloride permeability (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that hypertension in patients with WNK4 mutations is caused by increased NaCl reabsorption through the Na-Cl cotransporter and the paracellular pathway. It has also been reported that expression of long WNK1 abolishes the inhibition of the sodium chloride cotransporter caused by WNK4 (7). Long WNK1 activates serum-and glucocorticoid-inducible kinase, leading to activation of the epithelial Na + channel (ENaC; ref.…”
Section: Introductionmentioning
confidence: 99%